The effect of maximum and supramaximal strength exercises on developing motor response speed and the skill performance of spike for volleyball players - Yousif, Tariq (Journal of Physical Education, 2023)
The study aimed at the possibility of breaking the adjustment in the body muscles that are relevant to the volleyball player in terms of connectivity in the development of motor velocity through extreme and ultra-maximum force exercises. The researchers used the experimental method to solve the search problem. (24) A player in deliberate style, and the two researchers used several tools and methods, and this vocabulary was sunk for a period of.(4) weeks, 3 modules per week and 12 modules, 1 module time.(90 minutes) Motor speed measurement tests were used because of their importance in achieving the player's goal of exercise and the overwhelming strike test, which measures the performance level of offensive skills in volleyball. Tests were conducted before and after the use of extreme and super-maximum force exercises